Transplantation assessment of degraded Posidonia oceanica habitats: site selection and long-term monitoring - PIRROTTA, M.; TOMASELLO, A.; SCANNAVINO, A.; DI MAIDA, G.; LUZZU, F.; BELLISSIMO, G.; BELLAVIA, C.; COSTANTINI, C.; ORESTANO, C.; SCLAFANI, G.; CALVO, S. (Mediterranean Marine Science, 2014)
A model developed for Zostera marina was adapted and used to select suitable areas for Posidonia oceanica transplantation in the Gulf of Palermo, where recent rehabilitation programmes have reduced human pressure. This model consists of three steps: (1) habitat selection, by calculation of the Preliminary Transplant Suitability Index (PTSI); (2) field assessments and test-transplanting, to evaluate the site suitability and to estimate the effects of tearing on transplant units (about 50%); (3) identification of suitable restoration sites, by calculation of the Transplant Suitability Index (TSI). A new parameter was added to the literature model: the number of grids detached, which is linked to factors (hydrodynamic regime, anchoring, fishing) that have a potentially great effect on the final outcome of the transplant. Only one site (TSI = 16) in the Gulf of Palermo was indicated as potentially suitable for restoration with P. oceanica. In this site, a transplant of 40 m2 was implemented. From 2008 to 2014, transplant effectiveness was evaluated in terms of establishment, detachment and mortality of cuttings and shoot density. The long-term monitoring (6 years) allowed us to detect changes in the structural conditions of the transplanted meadow and to identify the possible turning point in P. oceanica recovery (2 years after transplanting). Moreover, 6 years after transplantation the P. oceanica meadow has exceeded the transplant shoot density of about 16%, with a mean and a maximum value of 11.6 and 17 shoots per cutting, respectively.